Utilization of Application-Based Technology for Strengthening Students’ Religious Character through the Hidden Curriculum - Indra, Syukri; Fauziah, R. Siti Pupu; Lathifah, Zahra Khusnul; Ramdhani, Muhammad Rendi; Kholik, Abdul; Fauziah, Namira (Bumi Publikasi Nusantara, 2026)
This study aimed to examine the utilization of an application-based Character Improvement System (CIS) to strengthen students’ religious character through integration with the hidden curriculum. A qualitative case study approach was employed, using interviews, observations, and documentation to collect data from teachers, students, and parents. The findings showed that the implementation of the hidden curriculum through religious practices was reinforced by CIS, which recorded, monitored, and rewarded students’ daily behaviors. The system encouraged discipline, honesty, and responsibility because every positive action was systematically appreciated and became a school habit. The integration of CIS with the hidden curriculum created measurable and transparent supervision that involved collaboration among teachers, parents, and students. This research contributes novelty by demonstrating how digital applications can support character formation beyond formal instruction. The impact is to provide schools with a replicable model for cultivating noble values consistently and sustainably.